Research trends in multimodal metaphor: a bibliometric analysis - Zhong, Zenan; Wen, Suijun; Chen, Shukun (Frontiers in Psychology, 2023)
This study reports a broad bibliometric overview of the published academic advances made in the field of multimodal metaphor during 1977 - 2022. This research imports a data set of 397 relevant publications retrieved from the Web of Science Core Collection (WoSCC) into VOSviewer to reveal the research trend based on publication features, i.e. year, author, country, participating journal and most cited reference, and research domain as shown by co-occurrence: key word plus. It is found that there is an overall increasing tendency in the total number of publications per year, with the year 2020 having the highest number (12.1%). This study also reveals significant patterns in citation authors, countries and journals as well as most cited references. The patterns in citation authors, countries and journals as well as most cited references are indicative of formative research groups that share similar research interests. As is evident from the screenshot generated from key word plus in co-occurrence, the research trends in multimodal metaphor during 1983 - 2022 fall into eleven coloured clusters. The most occurring keyword plus, besides “visual metaphor”, are “persuasion”, “pictures”, “impact”, “multimodal metaphor” and “model”. Nevertheless, we also identified three research trends, driven by cognitive linguistic theory, the theory of pragmatics and visual/multimodal rhetoric theory that may indicate possible directions for further research and are suggestive of new approaches for the study of multimodal metaphor.